2002
DOI: 10.1128/aem.68.10.4803-4808.2002
|View full text |Cite
|
Sign up to set email alerts
|

Replacement of Trifluoroacetic Acid with HCl in the Hydrophobic Purification Steps of Pediocin PA-1: a Structural Effect

Abstract: Trifluoroacetic acid (TFA) is a purification contaminant associated with pediocin PA-1 that interferes with Fourier transform infrared spectroscopy structural analysis. As revealed by circular dichroism, its presence affects the structural folding of pediocin. Consequently, we propose a new pediocin PA-1 purification procedure using HCl instead of TFA in all of the hydrophobic steps. This procedural change does not affect the purification yield or the amount of pediocin PA-1 purified. Furthermore, removing HCl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
73
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(82 citation statements)
references
References 44 publications
7
73
1
Order By: Relevance
“…The 54 -dependent transcription displays three specific features. First, 54 recognizes specific promoters with a particular consensus sequence, which is different from those recognized by the housekeeping 70 factor. Second, the promoter sequence is located at position Ϫ12/Ϫ24.…”
Section: Mode Of Action At the Molecular Levelmentioning
confidence: 99%
See 2 more Smart Citations
“…The 54 -dependent transcription displays three specific features. First, 54 recognizes specific promoters with a particular consensus sequence, which is different from those recognized by the housekeeping 70 factor. Second, the promoter sequence is located at position Ϫ12/Ϫ24.…”
Section: Mode Of Action At the Molecular Levelmentioning
confidence: 99%
“…In the case of the sakacin A producer Lactobacillus sakei 706, which harbors a three-component regulatory system, it has been shown that it is not possible to induce bacteriocin production by adding the inducer peptide VOL. 70,2006 CLASS IIa BACTERIOCINS 567 when this production has ceased due to growth near 37°C (49,139). Temperature-based regulation thus seems to overrule the quorum-sensing mechanism (139).…”
Section: Regulation Of Biosynthesismentioning
confidence: 99%
See 1 more Smart Citation
“…To date, several reports regarding the TFA toxicity against cells, e.g., suppression of proliferation of osteoblasts, were reported (Cornish et al 1999). In fact, counter-ions may also affect the secondary structure of peptides and proteins (Gaussier et al 2002). The presence of different counter-ions can affect hydrogen-bonding network and alter its structure (Blondelle et al 1995) (Cinelli et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Characterization of synthetic peptides, including conformational analysis, is routinely performed using IR and CD spectroscopy. However, a strong IR band at around 1670 cm −1 assigned to TFA which overlaps the amide I band of peptides (1600-1700 cm −1 ) may complicate analysis (Gaussier et al 2002). Several methods of peptide TFA − counter-ion exchange are described in the literature.…”
Section: Introductionmentioning
confidence: 99%